KINETIKA REAKSI PELARUTAN NIKEL DARI KALSIN NIKEL LATERIT [Kinetics of Nickel Dissolution from Nickel Laterite Calcine] - Subagja, Rudi (Jurnal Metalurgi, 2015)
At present work, an experiment to investigate a kinetics of nickel dissolution from nickel laterit calcine into the aqueous sulphuric acid solutions were carried out by using the nickel laterites calcine which was prepared by reduction roasting of nickel laterites oresby using 10% coal as reducing agents at temperature 800 °C. The dissolution test were caried out by using I litre capacities of glass reactor, with the experimental conditions: a) a sulphuric acid concentration 0,1 mole/litre, b) aeration rate were varied from 0 litre/menit up to 1 litre/menit, c)dissolution temperatures were varied from 40 °C up to 70 °C and reaction time were from 15 minutes up to 240 minutes. From the result of experiment, it is found that the dissolution of nickel from nickel laterite calcine into the aqueous sulphuric acid solutions increased when the aeration rate were increased from 0 litre/minute to I litre/minute, the dissolution temperatures were increased from 40 °C to 70 °C. From the kinetics study, it is found that the dissolution of nickel from nickel laterites calcines in to the aqueous sulphuric acid solutions follows the diffusion processcontrolled with activated energy 26.73 Kj/mole.